Analysis of Gender Dysphoria in Anna-Marie Mclemore's When The Moon Was Ours - Tri Rahayu, Imas; Andayani, Ambar (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2023)
This research is conducted to analyze gender dysphoria in Anna-Marie Mclemore’s When the Moon Was Ours where the emphasis is on the main character named Samir, a woman named Samira with different gender identity. Gender Dysphoria is a condition in which a person experiences discomfort with biological sex and feels pressure due to it. This research is conducted with the aim of revealing the reflections or characteristics as well as the causes and effects of gender dysphoria in this novel. This research uses the theory from A. Yarhouse to answer the characteristics and effects of gender dysphoria, and to find the causes the theory from Susan Stryker is applied. In addition, the writer also uses the theory of Queer from Butler as a support in formulating the problem. This research is a type of literature research that used descriptive qualitative method. The first research finding shows the reflections or characteristics of gender dysphoria experienced by the main character in the novel which refers to the discomfort between her gender and her gender identity, she has a desire to be a figure of another gender, and she has a desire to be treated as a figure of that gender. On the other hand, this also affects the feelings possessed by the main character who wants to have a distinctive feeling from another gender. Second, the causes of gender dysphoria experienced by the main character is caused by social and cultural factors which include the Pakistani tradition called Bacha Posh and the emotional dynamics of her family environment. Finally, the impacts of gender dysphoria experienced by Sam the main character in this novel are mental illness, attempting to end her life, feeling uncomfortable in the school environment, experiencing stigmatization and discrimination and tendency to isolate herself. Keyword: Gender Dysphoria, Gender Identity, Queer.